Mesenchymal stromal cell proliferation, gene expression and protein production in human platelet-rich plasma-supplemented media. - Paola Romina Amable (PLoS ONE, 2014)
BACKGROUND: Platelet-rich plasma (PRP) is increasingly used as a cell culture supplement, in order to reduce the contact of human cells with animal-derived products during in vitro expansion. The effect of supplementation changes on cell growth and protein production is not fully characterized. METHODS: Human mesenchymal stromal cells from bone marrow, adipose tissue and Wharton's Jelly were isolated and cultured in PRP-supplemented media. Proliferation, in vitro differentiation, expression of cell surface markers, mRNA expression of key genes and protein secretion were quantified. RESULTS: 10% PRP sustained five to tenfold increased cell proliferation as compared to 10% fetal bovine serum. Regarding cell differentiation, PRP reduced adipogenic differentiation and increased calcium deposits in bone marrow and adipose tissue-mesenchymal stromal cells. Wharton's Jelly derived mesenchymal stromal cells secreted higher concentrations of chemokines and growth factors than other mesenchymal stromal cells when cultured in PRP-supplemented media. Bone marrow derived mesenchymal stromal cells secreted higher concentrations of pro-inflammatory and pro-angiogenic proteins. Mesenchymal stromal cells isolated from adipose tissue secreted higher amounts of extracellular matrix components. CONCLUSIONS: Mesenchymal stromal cells purified from different tissues have distinct properties regarding differentiation, angiogenic, inflammatory and matrix remodeling potential when cultured in PRP supplemented media. These abilities should be further characterized in order to choose the best protocols for their therapeutic use.